East African Hip Hop: Youth Culture and Globalization. Mwenda Ntarangwi. 2009. Chicago: University of Illinois Press. appendix, glossary, index, 176 pp. - Amoros, Luis Gimenez (International Library of African Music, 2014)
pages: 154-157
Keywords: African Music